Legal instruments for strengthening the position of agricultural producers in the agri-food supply chain - Lipińska, Izabela (Przegląd Prawa Rolnego, 2024)
The article deals with issues regarding the protection of the position of an agricultural producer in the agri-food supply chain vis a vis significant differences that frequently occur in the bargaining power between suppliers and buyers of agricultural and food produce. These issues are analysed against the background of unfair trade practices. The aim of the article is to answer the question of whether the normative solutions adopted at the EU and at national levels serve to adequately strengthen the position of agricultural producers in the food supply chain. It ends with a conclusion that despite the existence of certain legal mechanisms supporting agricultural producers, the protection they provide is still insufficient.